Independent fiscal institutions A typology of OECD institutions and a roadmap for Latin America - Caldera Sánchez, Aida (OECD Economics Department Working Papers, 2024)
The paper reviews the diverse experience of OECD countries in establishing and running independent fiscal institutions, offering insights that could be useful for Latin American countries seeking to set-up and strengthen those institutions in the region. Through cluster analysis, we identify different types of OECD independent fiscal institutions and draw practical lessons from cases studies. We also identify key features that could serve as a road map for Latin American countries in their efforts to establish or enhance independent fiscal institutions